Impact of information and communication technology and financial development on economic growth of OPEC developing economies - Sepehrdoust, Hamid; Ghorbanseresht, Morteza (Kasetsart Journal of Social Sciences, 2018)
The main objective of present study was to investigate the impact of information and communication technology (ICT) and financial development on the developing economies of the petroleum exporting countries (OPEC) for the period 2002e2015 using a panel- GMM type of growth model. The results extracted from the econometric model showed that an increment of one percent in the financial development index and ICT variables caused economic growth to increase by .048 and .050 percent, respectively. Moreover, the impact of variables such as inflation (negative), active labor force growth (positive), investment growth (positive), and growth of gross fixed capital formation (positive) on the economic growth of the countries, were close to theoretical expectations. However, the impact of variables such as trade openness (negative) and government spending size (positive) on the economic growth of the selected countries did not support previous findings, perhaps because of the economic structural differences of the selected countries.